THERMOELECTRIC WASTE HEAT RECOVERY, AN ENVIRONMENTALLY FRIENDLY ENERGY SOURCE - Julio E. Rodríguez (Momento, 2010)
The price of fossil fuel accompanied by an increasing awareness of environmental problems associated with global warming, resulted in an upsurge of scientific activity to identify and develop environmentally friendly sources of electrical power. In this sense, direct energy conversion by thermoelectric devices using residual heat as heating source, could help to solve the energetic problems of the modern society. A thermoelectric converter is a solid state heat engine, in which the charge carriers are the work fluid, allowing the direct conversion of a thermal flow in electric power. This kind of devices are technologically attractive taking in to account that they do not have mobile parts, are silent, versatile and very reliable. Through last years the research of thermoelectric materials is focused on the development of thermoelectric generation systems, destined to optimize the low temperature waste heat recovery systems, which could generate useful electricity from different thermal sources as the human body, automobiles, and industrial plants. If the evolution of thermoelectric materials allows to improve the thermoelectric performance, in the next future these devices will contribute to reduce the use of fossil fuel and as a consequence to reduce the effects of global warming.